What’s the Future for Science in the New Zealand Curriculum? - Stewart GT; Eames C; Hipkins R; Cheng MMW; Birdsall S; Buntting C; Carpendale J; Edwards R; Hunt D; Swanson C (New Zealand Association for Research in Education, part of Springer Nature, 2024)
This commentary article considers the current contentious debates over the national school science curriculum in Aoteaora New Zealand. The co-authors of this commentary are members of a group of science teacher educators and science education researchers who met recently to discuss concerns over aspects of these debates in the context of a wider political contest over the control and direction of education policy.
Keywords: Curriculum Policy; Knowledge-Rich Curriculum; PISA; Science Education; Scientific Literacy